Entrepreneurial Self-Efficacy on Digital Entreprenur Readiness - Rinawan, Rangga Bayu; Suswanto, Hary; Larasati, Aisyah (Jurnal Pendidikan Humaniora, 2020)
Abstract: Entrepreneurial Self Efficacy (ESE) and entrepreneurship are currently receiving special attention from researchers and decision makers. Various responses are carried out by empowering vocational students to be equipped with skills that are in line with current industry needs. Thinking, entrepreneurial behavior and ESE will help students take responsibility so as to achieve success and adapt to social progress and change. The 4.0 industrial revolution era has a great opportunity to engage in the business world. Digital Entrepreneurship is created by using technology appropriately and it is very possible for vocational students.Keywords:Â entrepeneurship, self-efficacy, digital entrepreneur, studentAbstrak: Entrepreneurial Self Efficacy (ESE) dan wirausaha saat ini mendapatkan perhatian khusus dari para peneliti dan pembuat keputusan. Berbagai respon dilakukan dengan memberdayakan siswa SMK untuk dibekali dengan keterampilan yang sesuai dengan kebutuhan industri saat ini. Pemikiran, perilaku wirausaha dan ESE akan membantu siswa bertanggung jawab sehingga mencapai kesuksesan dan beradaptasi dengan kemajuan serta perubahan sosial. Era revolusi industir 4.0 memiliki peluang besar untuk berkecimpung di dunia usaha. Digital Entrepreneurhsip tercipta dengan pemanfaatan teknologi dengan tepat dan hal tersebut sangat mungkin terjadi untuk siswa SMK.Kata kunci:Â kewirausahaan, efikasi diri, kewirausahaan digital, siswa